Enhancing flexibility evaluation in AC/DC distribution systems for sustainable energy integration - Wang, Luyang; Zhao, Qianyu; Wang, Shouxiang; Jiang, Xingyue (Frontiers in Energy Research, 2024)
With the exacerbation of environmental issues and the ongoing energy crisis, the large-scale integration of renewable energy resources has significantly increased the demand for flexibility in distribution systems. Establishing a comprehensive flexibility evaluation index system is crucial for the development, promotion, and optimization of AC/DC distribution systems. This paper focuses on the flexibility evaluation of AC/DC distribution systems, proposing a detailed flexibility evaluation index system and a comprehensive evaluation method based on the ANP-Entropy weighting model. The proposed flexibility evaluation index system comprises 18 key indexes categorized into four essential dimensions: overall flexibility performance, flexible resources participation, operational performance, and economic performance. The ANP-Entropy weighting model is employed to perform a thorough evaluation of the flexibility of AC/DC distribution systems. To validate the effectiveness of the proposed evaluation method, a case study is conducted. Additionally, the study explores the impacts of controllable distributed generator (CDG) capacity, energy storage system (ESS) capacity, and voltage source converter (VSC) capacity on the flexibility of AC/DC distribution systems. The results provide valuable insights into optimizing the flexibility and performance of AC/DC distribution systems.